CREATION OF SUB-COMMITTEES FOR THE EXECUTIVE OF THE HISTORICAL ASSOCIATION OF S.A. (Historia, 2021)
Following the example of among others the Organisation of American Historians and the American History Association to use sub-committees to function more effectively, it was decided at a meeting of the Executive of the Association, held on 22 June 2001, to implement a similar method for the Association. Eight possible sub-committees, as well as possible conveners, were identified. The method to be followed is that the different conveners will contact other members of the Executive and historians to become involved with the sub-committees. Members of the Executive were already placed in certain sub-committees. Matters of importance will be referred to the different sub-committees via the Executive, but sub-commitees can also inform the Executive of important issues that need to be addressed.
Keywords: Organisation of American Historians; subject in schools; geography; local and regional history; GET phase